KINERJA INSPEKTORAT DAERAH PROVINSI SULAWESI UTARA - Rantung, Margareth I.R; Tarore, Steven V; Posumah, Esther (Jurnal Administrasi Publik dan Kebijaka (JAPK), 2023)
This study aims to determine and describe the performance of the North Sulawesi Regional Inspectorate. The research method used is qualitative descriptive. The number of informants in this study were 4 people. Data collection uses observation, interview and documentation techniques. Data analysis through Data Reduction, Data Presentation and Drawing Conclusions. The results of the study show that based on the results of the research and discussion related to the performance of the North Sulawesi Regional Inspectorate, it can be concluded that employees at the North Sulawesi regional inspectorate office in terms of carrying out the supervisory function have not been maximized, this can be seen from the following indicators. 1) Productivity Performance is not good enough. Performance Quality that shows the development of each employee. 3) The accuracy is not yet effective because it is influenced by several factors. Penelitian ini bertujuan untuk mengetahui dan mendeskripsikan kinerja Inspektorat Daerah Sulawesi Utara. Metode penelitian yang digunakan adalah deskriptif kualitatif. Jumlah informan dalam penelitian ini sebanyak 4 orang. Pengumpulan data menggunakan teknik observasi, wawancara dan dokumentasi. Analisis data melalui Reduksi Data, Penyajian Data dan Penarikan Kesimpulan. Hasil penelitian menunjukkan bahwa berdasarkan hasil penelitian dan pembahasan terkait dengan kinerja Inspektorat Daerah Sulawesi Utara dapat disimpulkan bahwa pegawai pada kantor inspektorat daerah Sulawesi Utara dalam hal menjalankan fungsi pengawasan belum maksimal, hal ini dapat dilihat dari beberapa indikator sebagai berikut 1) Kinerja Produktivitas belum cukup baik. Kualitas Kinerja yang menunjukkan perkembangan setiap pegawai. 3) Ketepatan yang belum efektif karena dipengaruhi oleh beberapa faktor.